Embolization of large spontaneous portosystemic shunts for refractory hepatic encephalopathy: A multicenter survey on safety and efficacy1. Issue 6 (1st May 2013) - Laleman, Wim; Simon‐Talero, Macarena; Maleux, Geert; Perez, Mercedes; Ameloot, Koen; Soriano, German; Villalba, Jordi; Garcia‐Pagan, Juan‐Carlos; Barrufet, Marta; Jalan, Rajiv; Brookes, Jocelyn; Thalassinos, Evangelos; et al.
Abstract Refractory hepatic encephalopathy (HE) remains a major cause of morbidity in cirrhosis patients. Large spontaneous portosystemic shunts (SPSSs) have been previously suggested to sustain HE in these patients. We aimed to retrospectively assess the efficacy and safety of patients treated with embolization of large SPSSs for the treatment of chronic therapy‐refractory HE in a European multicentric working group and to identify patients who may benefit from this procedure. Between July 1998 and January 2012, 37 patients (Child A6‐C13, MELD [Model of Endstage Liver Disease] 5‐28) with refractory HE were diagnosed with single large SPSSs that were considered eligible for embolization. On a short‐term basis (i.e., within 100 days after embolization), 22 out of 37 patients (59.4%) were free of HE (P < 0.001 versus before embolization) of which 18 (48.6% of patients overall) remained HE‐free over a mean follow‐up period of 697 ± 157 days (P < 0.001 versus before embolization). Overall, we noted improved autonomy, decreased number of hospitalizations, and severity of the worst HE episode after embolization in three‐quarters of the patients. Logistic regression identified the MELD score as strongest positive predictive factor of HE recurrence with a cutoff of 11 for patient selection. As to safety, we noted one major nonlethal procedure‐related complication. There was no significant increase in de novo development or aggravation of preexisting varices, portal hypertensive gastropathy, or ascites. Conclusion: This multicenter European cohort study demonstrated a role for large SPSSs in chronic protracted or recurrent HE and substantiated the effectiveness and safety of embolization of these shunts, provided there is sufficient functional liver reserve. (HEPATOLOGY 2013;57:2448–2457)